Central Sensıtızatıon ın Axıal Spondyloarthrıtıs: An Exploratıve Study wıth Quantıtatıve Sensory Testıng and Clınıcal Scales - DURUÖZ, MEHMET TUNCAY (My University, 2021)
OBJECTIVE: To evaluate the central sensitization (CS) and the related parameters in patients with axial spondyloarthritis (axSpA). METHODS: Quantitative sensory testing (QST) which consists of pressure pain threshold (PPT), temporal summation (TS), and conditioned pain modulation (CPM) were applied to the participants. Disease activity, functional status, sleep quality, pain, depression, and fatigue were assessed. Patients were divided as the ones with and without CS according to the central sensitization inventory (CSI) and the results were compared. RESULTS: One hundred patients and fifty controls were recruited. Sixty axSpA patients had CS. When QST results were compared between the patient and control groups, all PPT scores were found lower (p<0.05) in patients. Regarding the comparison of the patients with and without CS, sacroiliac, and trapezius PPT scores were found lower in the patients with CS (p<0.05). On the other hand, there was no significant difference in the mean TS scores (p>0.05) between patients and controls, and in patients with and without CS. All investigated comorbidities were found to be significantly more frequent (p<0.001) in the patients with CS. In regression analysis female gender, morning stiffness duration, CPM, depression, and fatigue were detected as related parameters with CSI scores. CONCLUSION: CS and related comorbidities were found to be increased in axSpA patients. This increase should be taken into consideration in the management of these patients.
Keywords: Axial spondyloarthritis; central sensitization; central sensitization inventory; quantitative sensory testing